Methodological approach to qualitative research of depersonalization of moral agent in online environment - Tomoriová, Františka (Qualitative and Quantitative Methods in Libraries, 2019)
Moral agent in online environment behaves differently than he would behave in offline environment. Moral agent's actions may seem to him to be not real and dream-like, perceived even as a role play and not part of real life (Floridi 2013). The reasons are numerous, for example anonymity in online environment. Depersonalization has been studied using both qualitative and quantitative research methods, focusing mainly on research of verbal communication in online environment in comparison with offline environment. However there seems to be more space for research done in the area of situational context and in the context of information ethics.